Reliability modeling and analysis of the polymer transformation process of a sanitising industry - Alcantara, Murilo Leite (2015)
The sanitizing industry has had a growing importance in the Brazilian industrial sector. One of the most important steps for most of the sanitizing industries is the production processes of bottles. The production of these bottles is usually carried out through polymer processing methods such as extrusion and blow molding. In order to increase the industrial production safely, it is necessary to use methods to reduce the occurrence of failures. The study of production systems reliability can be used as a tool to understand and predict the behavior of industrial units’ failures. This paper studies the reliability behavior of a sanitizing industry with the focus on the bottles production. This study was based on three modeling methodologies: Global Life Distribution (GLD), Composite Life Distribution (CDL) and Optimum Composite Life Distribution (OCDL). The distributions used were: exponential, Weibull, normal, lognormal, q-exponential and q- Weibull. The reliability behaviors found by these three methodologies were compared with the reliability obtained experimentally. The OCLD methodology overcomes the limitations of both GLD and CLD methodologies, but inherits their strengths. The OCDL methodology resulted in a good representation of the subsystems as well as the overall system behavior. It is also carried out in this paper an analysis of the contribution of the subsystems to the overall probability of system failure. The outgoing profit was calculated and it is a potential indicative of financial benefit that can be obtained with possible future developments of the study.